2022
DOI: 10.7759/cureus.24585
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Response of Patients With Autoimmune Rheumatic Disease to BNT162b2 Vaccine: A Retrospective Comparative Study

Abstract: Objective The effectiveness and safety of SARS-CoV-2 vaccines in patients with autoimmune rheumatic diseases (ARDs) treated with immunomodulators remain uncertain. Therefore, this study aimed to evaluate whether the humoral immune response to the BNT162b2 vaccine differs between patients without and with ARDs treated with immunomodulators. Methods We retrospectively reviewed 3208 electronic medical records from the database of the Hamad Medical Corporation (HMC) outpatient rheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The high level of COVID-19 vaccine immunogenicity in patients with ARD is consistent with other studies as well [56] , [57] . A recent systematic review and meta-analysis by Tang et al showed that patients with ARD achieved seroconversion in 79 % (95 %CI: 67–89 %), and cellular response in 69 % (95 %CI: 55–81 %) after the second dose of mRNA-vaccine [56] .…”
Section: Discussionsupporting
confidence: 91%
“…The high level of COVID-19 vaccine immunogenicity in patients with ARD is consistent with other studies as well [56] , [57] . A recent systematic review and meta-analysis by Tang et al showed that patients with ARD achieved seroconversion in 79 % (95 %CI: 67–89 %), and cellular response in 69 % (95 %CI: 55–81 %) after the second dose of mRNA-vaccine [56] .…”
Section: Discussionsupporting
confidence: 91%
“…A study in India reported a negative association between antispike antibody titers and DM in addition to a shorter dosing interval of 4 weeks between the two doses of AZD1222 (Aztra-Zenaca/ChAdOx1) vaccine in a cohort of 561 patients with RDs [54]. The presence of DM did not influence the response to BioNtech mRNA vaccine as reported in a study from Qatar in 100 patients with RDs [55]. Another study in Greece in a cohort of 605 patients with RDs revealed that 88% developed a humoral immune response to mRNA vaccines with age and comorbidities having no influence on the response.…”
Section: Immune Response To Infection and Vaccinationmentioning
confidence: 78%
“…Studies have also analyzed the effects of DM in RDs on the humoral immune response to SARS-CoV-2 vaccines [55][56][57]. A study in India reported a negative association between antispike antibody titers and DM in addition to a shorter dosing interval of 4 weeks between the two doses of AZD1222 (Aztra-Zenaca/ChAdOx1) vaccine in a cohort of 561 patients with RDs [54].…”
Section: Immune Response To Infection and Vaccinationmentioning
confidence: 99%